2023
DOI: 10.1021/acsomega.3c02955
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Bis-tetraphenylethene as a Novel Turn-On Selective Zinc Sensor

Abstract: The main purpose of this study is the synthesis of novel fluorescent Bis-TPE and the investigation of its wide range of photochemical behaviors. For this purpose, initially, Bis-TPE was synthesized. Following this, the interactions of Bis-TPE with a wide range of ions were studied in EtOH using ultraviolet–visible (UV–vis) and fluorescence spectroscopy. As a result of all UV–vis and fluorescence studies, it was determined that Bis-TPE showed turn-on sensor features against Zn2+ ions. Moreover, the limit of det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…This AIE behavior likely results from reduced photoinduced electron transfer as TPEs disaggregate in water due to their nucleophilic nitrogen (N) and oxygen (O) groups ( Figure 6 A). 56 Reversible binding was confirmed by alternating Cu 2+ and GSH additions, which respectively quenched and restored fluorescence ( Figure 6 B). TPEs samples, soft yellow and pale-orange solids, exhibit distinct emissions from TPEs–Cu 2+ complexes, likely as a result of copper interfering with the π–π* transitions of the TPE moiety ( Figure 6 C).…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…This AIE behavior likely results from reduced photoinduced electron transfer as TPEs disaggregate in water due to their nucleophilic nitrogen (N) and oxygen (O) groups ( Figure 6 A). 56 Reversible binding was confirmed by alternating Cu 2+ and GSH additions, which respectively quenched and restored fluorescence ( Figure 6 B). TPEs samples, soft yellow and pale-orange solids, exhibit distinct emissions from TPEs–Cu 2+ complexes, likely as a result of copper interfering with the π–π* transitions of the TPE moiety ( Figure 6 C).…”
Section: Resultsmentioning
confidence: 84%
“…First, AIE studies demonstrated increased TPEs emissions with higher water content. This AIE behavior likely results from reduced photoinduced electron transfer as TPEs disaggregate in water due to their nucleophilic nitrogen (N) and oxygen (O) groups (Figure A) . Reversible binding was confirmed by alternating Cu 2+ and GSH additions, which respectively quenched and restored fluorescence (Figure B).…”
Section: Resultsmentioning
confidence: 93%
“…For instance, zinc is frequently found in red blood cells (RBCs) as an essential element of the enzyme carbonic anhydrase (hCAs), which plays a vital role in carbon dioxide metabolism processes. 3…”
Section: Introductionmentioning
confidence: 99%
“…10 Abnormal concentration of zinc can affect the growth and development of mammals (including humans) and plants, leading to several diseases such as Parkinson's disease, Alzheimer's disease (AD), arteriosclerosis, brain diseases, hair loss, stomach disorders, diarrhoea, epilepsy, cataract, ischemic stroke and night blindness. 3,11…”
Section: Introductionmentioning
confidence: 99%